The nature of hydrogen-bonding interaction in the prototypic hybrid halide perovskite, tetragonal CH(3)NH(3)PbI(3) - Lee, June Ho (Sci Rep, 2016)
In spite of the key role of hydrogen bonding in the structural stabilization of the prototypic hybrid halide perovskite, CH(3)NH(3)PbI(3) (MAPbI(3)), little progress has been made in our in-depth understanding of the hydrogen-bonding interaction between the MA(+)-ion and the iodide ions in the PbI(6)-octahedron network. Herein, we show that there exist two distinct types of the hydrogen-bonding interaction, naming α- and β-modes, in the tetragonal MAPbI(3) on the basis of symmetry argument and density-functional theory calculations. The computed Kohn-Sham (K-S) energy difference between these two interaction modes is 45.14 meV per MA-site with the α-interaction mode being responsible for the stable hydrogen-bonding network. The computed bandgap (E(g)) is also affected by the hydrogen-bonding mode, with E(g) of the α-interaction mode (1.73 eV) being significantly narrower than that of the β-interaction mode (2.03 eV). We have further estimated the individual bonding strength for the ten relevant hydrogen bonds having a bond critical point.